Catheter based renal sympathetic denervaton: treatment option for resistant hypertension - Dhital, BM; Mao, Ou Yang; Deep, JP; Rauniyar, VK (Journal of College of Medical Sciences-Nepal, 2012)
Essential hypertension being a major public health problem with an atrocious toll. Furthermore resistant hypertension has increased morbidity and mortality in spite of using three or more antihypertensive medication, including one diuretic at their optimal doses to achieve the target blood pressure. Renal artery with its sympathetic afferent and efferent nerve signaling has substantial role in elevating and sustaining blood pressure. Blunting the overt sympathetic activity, catheter based renal sympathetic nerve denervation has become new treatment approach for the treatment of resistant hypertension. So in this review we address the current aspect and development of renal sympathetic denervation in the management of difficult to control hypertension. Journal of College of Medical Sciences-Nepal,2012,Vol-8,No-2, 58-63 DOI: http://dx.doi.org/10.3126/jcmsn.v8i2.6841